2018
DOI: 10.1097/jnn.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

Complications Associated With Nasogastric Tube Placement in the Acute Phase of Stroke: A Systematic Review

Abstract: This systematic review explores the frequency of complications associated with nasogastric tube (NGT) placement in patients with acute stroke. The unique condition of the dysphasic, immobile, confused immunosuppressed patient who has had an acute stroke hampers any consistent inference from other neurological or nonneurological condition in which NGT placement is used. Twelve studies including 921 patients fed by NGT in the acute phase (first 4 weeks) were included in the analysis. The overall quality of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Several studies addressed the role of NGT as a risk factor for pneumonia but with contrasting results due to the absence, as in our study, of specific analysis on the number of NGT used per patient during the hospitalization [ 44 ]. Anyway, the presence of a high gastric residual volume, coupled with stroke-induced deglutition impairments, may easily lead to aspiration of gastric content in the lungs [ 45 ]. Moreover, both dislodgement of the tube and the repetition of the positioning procedure are risk factors for developing pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies addressed the role of NGT as a risk factor for pneumonia but with contrasting results due to the absence, as in our study, of specific analysis on the number of NGT used per patient during the hospitalization [ 44 ]. Anyway, the presence of a high gastric residual volume, coupled with stroke-induced deglutition impairments, may easily lead to aspiration of gastric content in the lungs [ 45 ]. Moreover, both dislodgement of the tube and the repetition of the positioning procedure are risk factors for developing pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review on the topic noted that only 6 of 12 papers on the topic described NGT placement failure and malposition [14]. The authors concluded "Data are scarce on the topic.…”
Section: Complicationsmentioning
confidence: 99%
“…Research about the frequency of local and systemic NGT complications and strategies for prevention will certainly contribute to enhance evidence-based management of dysphagia in acute stroke" [14]. Search for specific terms relating to chest complications were not found in the papers reviewed in this meta-analysis [14]. By contrast, NGT insertion was better documented outside of the stroke literature [15][16][17][18][19].…”
Section: Complicationsmentioning
confidence: 99%
“…Enteric feeding is, in situations of severe dysphagia, the only way to ensure nutritional and hydration intake, as well as allowing the administration of medication [69]. However, its use is not without risks, with mechanical complications, such as nasal trauma, displacement, poor positioning and obstruction [70], gastrointestinal complications [71], metabolic disorders [72], resulting in a worse quality of life [73]. Different international guidelines recommend as soon as possible enteral nutrition by NGT in patients who, after a stroke, do not swallow safely, with recommendations varying between the first 24 h [18], the first 3 days [17,19,21] or the first 7 days [16,22,27].…”
Section: Summary Of Evidencementioning
confidence: 99%